2022
DOI: 10.1039/d2cc00245k
|View full text |Cite
|
Sign up to set email alerts
|

Co–NCNT nanohybrid as a highly active catalyst for the electroreduction of nitrate to ammonia

Abstract: Electrocatalytic nitrate (NO3−) reduction has emerged as an attractively dual-function strategy to produce ammonia (NH3) and simultaneously mitigate environmental issues. However, efficient electrocatalysts with high selectivity for NH3 synthesis are...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 50 publications
(47 reference statements)
1
8
0
Order By: Relevance
“…21(f)). This demonstrates the Co(111) surface's high activity and selectivity, which is consistent with the findings of another study reported by our group [408]. Charge analyses also revealed that surface Co atoms offered electrons to the N or O of nitrogen-containing intermediates to bond these intermediates.…”
Section: Electrochemical Reduction Of Nitrogen Oxyanionssupporting
confidence: 91%
See 2 more Smart Citations
“…21(f)). This demonstrates the Co(111) surface's high activity and selectivity, which is consistent with the findings of another study reported by our group [408]. Charge analyses also revealed that surface Co atoms offered electrons to the N or O of nitrogen-containing intermediates to bond these intermediates.…”
Section: Electrochemical Reduction Of Nitrogen Oxyanionssupporting
confidence: 91%
“…Our group experimentally demonstrated Co's high intrinsic activity and made significant progress by developing various Co catalysts such as Co-NCNT [408], Co-decorated pomelopeel-derived carbon [409], Co-decorated Juncus-derived carbon [410], Co-P alloy [413], Fe-doped Co3O4 nanoarray [411], and Co-containing spinels such as NiCo2O4 [414] and Co2AlO4 [415]. Wang's group also demonstrated that Co was active enough for NO3RR to produce NH3 (Fig.…”
Section: Electrochemical Reduction Of Nitrogen Oxyanionsmentioning
confidence: 97%
See 1 more Smart Citation
“…In addition to the intrinsic eNO 3 RR activity, a chief side hydrogen evolution reaction (HER) can compete with the eNO 3 RR, which consumes electrons and protons, and thus subsequently reduces the energy efficiency and FE. 2,10,[43][44][45][46][47] As shown in Fig. 5, adsorbing H on the Zn@BN and Zn@BN/GR is thermodynamically unfavourable with a large uphill adsorption free energy of 1.06 and 1.05 eV.…”
mentioning
confidence: 99%
“…Besides, Co-based materials have been demonstrated to possess strong catalytic reduction activity for electrochemical NO 3 − -to-NH 3 conversion. 33–35 Therefore, a metallic Co/N-doped carbon composite derived from a bio-MOF consisted of Co 2+ ions and adenine is expected as an attractive electrocatalyst for the NO 3 RR.…”
mentioning
confidence: 99%